The millennials' transition from school-to-work - Audra J. Bowlus; Yuet-Yee Linda Wong (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2020)
We present the first study of the high school-to-work transition for American Mil- lennial males and females. Using data from the PSID Transition to Adulthood from 2005-2011, we estimate the Burdett and Mortensen (1998) model and study changes between Generation X and Millennials. We find convergence in racial differences in transition patterns across the generations and in gender earnings by the Great Reces- sion. These patterns are driven by a large decline in search efficiencies for white males. Finally, we show the labor market deteriorated for high school graduates prior to, with a further decline during, the Great Recession.
Keywords: 330; Millennials; school-to-work; search frictions; early career outcomes